Penguatan Model Dakwah Komunitas di Pimpinan Cabang Muhammdiyah Banguntapan Selatan Bantul DIY - Fathurrahman, Ayif (MAYARA: Jurnal Pengabdian Masyarakat, 2025)
Muhammadiyah PPM activities are carried out at PCM Banguntapan Selatan, Bantul, targeting the elderly who live in the PCM Banguntapan Selatan environment. The conditions of the elderly in the Banguntapan environment are very diverse, but one thing that must be underlined is that they are people who need to be accompanied, not only because of physical problems that are getting older but also because of circumstances that are no longer crowded when they were young, when they could still interact with friends regularly. And most importantly, how can we be consistent with religious values? So, a community that can restore happy memories, closeness and enthusiasm in practising religion is a real need. The implementation of this service activity includes: 1) Providing material about Islam and Health; 2) Holding SEHATI gymnastics regularly as a forum. Results: The realisation of the effectiveness of community-based preaching. Second. Increasing understanding of maintaining health from an Islamic perspective with the concept of halal-thoyyiban. Community-based preaching is a preaching method developed by PCM Banguntapan that targets the elderly who live in South Banguntapan, including Potorono, Jambidan, and Wirokerten. This was chosen for several reasons, including the need for a forum to form a community together. This togetherness has created intimacy, joy and has a positive impact on physical and spiritual health.